(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article provides a theoretical and analytical study of the linguistic methodology of scientific term formation in the Arabic language. The research examines the role of terminology in Arabic linguistics, its close relationship with morphology (ṣarf) and syntax (naḥw), and its significance in ensuring precision and unambiguity in the expression of scientific concepts. The article explores the formation of the concept of “term,” the process of semantic transition from lexical meaning to scientific and terminological meaning, and analyzes the main methods used in scientific term formation – derivation, analogy, metaphor, Arabization, compounding, and semantic generation – from a linguistic perspective. In addition, the study highlights the role of norms and principles developed by Arabic language academies in systematizing and unifying scientific terminology. The findings confirm that the internal linguistic resources of Arabic possess sufficient potential for the creation of scientific terminology and its adaptation to the requirements of modern science.